Physics of Metals and Metallography - Ustinov, Vladimir V.; SpringerLink (Online service) (Moscow : Pleiades Publishing : Imprint: Pleiades Publishing.)
The Physics of Metals and Metallography (Fizika metallov i metallovedenie) was founded in 1955 by the USSR Academy of Sciences. Its scientific profile covers the theory of metals and metal alloys, their electrical and magnetic properties, as well as their structure, phase transformations, and principal mechanical properties. The journal publishes scientific reviews and papers written by experts involved in fundamental, application, and technological studies. The annual volume of publications amounts to 250 papers submitted from 100 leading national scientific institutions.
Keywords: Metals; Metallic Materials